Regional Autonomy in the Context of the Unitary State of Indonesia: Evaluation of Household Systems, Measurement Parameters, and the Rationality of Decentralization - Fadiah; suhaimi, nurnisaa; Laksito, Grida Saktian (Communication in Research and Publications (CRP), 2024)
Regional autonomy in the context of the unitary state of Indonesia is a phenomenon based on constitutional foundations, especially Article 18 paragraph (1) of the 1945 Constitution. This discussion examines the regional household system, parameters for measuring regional autonomy, as well as the rationality and arguments supporting decentralization. The regional household system, consisting of material, formal and real, raises considerations regarding the granting of autonomous rights to regions. The measurement parameters involve authority quotas, supervision systems, methods for selecting regional heads, and the process of making regional regulations, but further clarification is needed. The rationality of regional autonomy includes efficiency, political education instruments, strengthening political stability, political equality, preparation for political careers, and accuracy of development planning. Arguments supporting decentralization highlight the prevention of accumulation of power, popular participation, government efficiency, adaptation to regional specificities, and direct assistance for development. Strengthening regional autonomy requires regulatory capabilities, adjustments to national regulations, local political support, financial resources, and human resource development. This research reflects efforts to understand, evaluate and strengthen regional autonomy systems to support regional development and national stability.